Management of patulous Eustachian tube dysfunction following bariatric surgery: a case report - Youssef Arkoubi, Amr (Frontiers in Surgery, 2025)
Patulous Eustachian Tube (PET) dysfunction is a rare condition characterized by an abnormally open Eustachian tube, leading to symptoms such as autophony, auditory fullness, and pulsatile tinnitus. This case report describes a 48-year-old female weighing 72.4 kilograms who developed persistent autophony and hearing her own breathing and heartbeat sounds following significant weight loss after sleeve gastrectomy. Initial treatments, including bilateral ventilation tubes, provided minimal relief. Diagnosis of PET was established through clinical and nasopharyngeal examination in the ear, nose and throat (ENT) department, revealing bilaterally open Eustachian tubes with a pronounced defect on the left ear. Surgical management included removal of the ventilation tubes, bilateral balloon dilation of the Eustachian tubes, and fat injection with plasma into the tubal opening (medial), utilizing fat harvested via liposuction. The patient was observed to have stable condition when her weight is above 80 kilograms, but the symptoms recurred while being under 80 kilograms, therefore her PET dysfunction was weight dependent. Postoperative outcomes showed temporary symptomatic relief lasting six months, with partial symptom recurrence. This case highlights the role of combined surgical interventions in managing PET and underscores the need for further research to develop durable treatment solutions for this challenging condition.